2010
DOI: 10.1038/nature09144
|View full text |Cite
|
Sign up to set email alerts
|

A coding-independent function of gene and pseudogene mRNAs regulates tumour biology

Abstract: The canonical role of messenger RNA (mRNA) is to deliver protein-coding information to sites of protein synthesis. However, given that microRNAs bind to RNAs, we hypothesized that RNAs possess a biological role in cancer cells that relies upon their ability to compete for microRNA binding and is independent of their protein-coding function. As a paradigm for the protein-coding-independent role of RNAs, we describe the functional relationship between the mRNAs produced by the PTEN tumour suppressor gene and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

47
2,011
6
16

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,135 publications
(2,119 citation statements)
references
References 52 publications
47
2,011
6
16
Order By: Relevance
“…Poliseno and colleagues revealed that the PTENP1 3′UTR significantly suppressed cell proliferation in PTEN‐null PC3 cells, supporting the notion that PTENP1 could exert a tumour‐suppressive role independent of the parent PTEN gene 2. Likewise, ψPPM1K, a partial retrotranscript pseudogene containing inverted repeats capable of being processed into two endo‐siRNAs, regulates cell growth‐related target genes and exerts tumour‐suppressive activity independent of its cognate gene PPM1K 3.…”
Section: Discussionmentioning
confidence: 88%
“…Poliseno and colleagues revealed that the PTENP1 3′UTR significantly suppressed cell proliferation in PTEN‐null PC3 cells, supporting the notion that PTENP1 could exert a tumour‐suppressive role independent of the parent PTEN gene 2. Likewise, ψPPM1K, a partial retrotranscript pseudogene containing inverted repeats capable of being processed into two endo‐siRNAs, regulates cell growth‐related target genes and exerts tumour‐suppressive activity independent of its cognate gene PPM1K 3.…”
Section: Discussionmentioning
confidence: 88%
“…[176][177][178] Although PTEN promoter methylation has been reported, 179 an unknown but probably high proportion of these findings relate to cross-reactions with the pseudogene PTENP1. 180 Studying prostatic cancer, Pandolfi and co-workers 181,182 have shown PTENP1 to be transcribed and have provided evidence indicating it may act as a decoy, competing with the PTEN transcript for miRNA binding. If these findings are confirmed in other cancer forms as well, it may have significant implications to our understanding of PTEN regulation, but probably regulation of other genes as well.…”
Section: Activating Mutations In the Pten/pi3k/mtor Pathway As A Causmentioning
confidence: 99%
“…The tumor suppressor phosphatase and tensin homologue deleted on chromosome 10 (PTEN) is involved in CoGAM The tumor suppressor PTEN, a major inhibitory regulator of the PI3K/AKT proliferation signaling pathway (Carracedo and Pandolfi, 2008), is also a shared target of miR-19 (Lewis et al, 2003) and miR-20 (Poliseno et al, 2010). In addition, in MDA-MB-231 cells, the PTEN protein was actually significantly increased by Drosha knockdown (Figure 5a), a result that was confirmed at the mRNA level ( Supplementary Figure 8).…”
Section: Identification Of Microprocessor-dependent Cancer Cellsmentioning
confidence: 99%